Anthraquinone Rhein Exhibits Antibacterial Activity against Staphylococcus aureus - Federica Dell’Annunziata; Veronica Folliero; Francesca Palma; Valeria Crudele; Emiliana Finamore; Giuseppina Sanna; Aldo Manzin; Anna De Filippis; Massimiliano Galdiero; Gianluigi Franci (Applied Sciences, 2022)
Staphylococcus aureus (S. aureus) represents an important pathogen of clinical relevance, causing a wide variety of symptoms. The broad distribution of multidrug-resistant strains necessarily demands new antibacterial agents for the treatment of S. aureus infections. The aim of this study was to assess the antibacterial activity of plant-derived compounds, pure 4,5″-dihydroxy-anthraquinone-2-carboxylic acid (Rhein), against standard and clinical isolated S. aureus strains. The hemolysis and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assays were used to determine the cytotoxicity on human erythrocytes and bronchial epithelial cells after treatment with Rhein. The antibacterial effect was assessed via disk diffusion test, broth microdilution methods, time-killing assays and live–dead evaluation (50–0.39 µg/mL). Rhein effect on the hemolytic activity of α-toxin and catalase were estimated. Moreover, crystal violet (CV) assay evaluated its impact on biofilm biomass. The compound exhibited 50% cytotoxic concentration (CC50) and 50% hemolysis concentration (EC50) of 43.6 and >50 µg/mL, respectively. The minimum inhibitory concentration (MIC) of Rhein was 12.5 µg/mL for all tested strains, exerting bacteriostatic action. MIC and sub-MIC concentrations of Rhein significantly reduced hemolytic and catalase activities, impairing the major virulence factors of S. aureus strains. Rhein also reduced biofilm biomass in a dose-dependent manner, reaching rates of about 50% eradication at a dose of 50 µg/mL. These findings suggest that Rhein could represent a promising therapeutic option for the treatment of S. aureus infections.